Polymorphisms C677T and A1298C of MTHFR Gene: Homocysteine Levels and Prothrombotic Biomarkers in Coronary and Pulmonary Thromboembolic Disease - Lupi-Herrera, Eulo (Clin Appl Thromb Hemost, 2018)
The activity of the enzyme methylenetetrahydrofolate reductase (MTHFR) determines homocysteine (Hcy) levels, and polymorphisms in its gene affect the activity of the enzyme. Changes in the enzyme’s activity may lead to a higher susceptibility to develop arterial and venous thromboembolic disease. The aim was to analyze the relationship between the C677T and A1298C polymorphisms of MTHFR, Hcy levels, and prothrombotic biomarkers in pulmonary embolism (PE) and acute myocardial ischemia (AMI). Clinical files of patients with thromboembolic diseases having complete data and whose doctor had requested an assay to determine the polymorphisms of the MTHFR gene, Hcy levels, and prothrombotic biomarkers were studied to search for the correlation between mutations of the MTHFR gene and Hcy levels in the different diseases. We included 334 files: 158 were from women and 176 from men (51 [19 SD] years). Sixty-three percent have had thrombosis, 8% AMI, and 31% PE. Patients with thrombosis had elevated frequency of the C677T polymorphism. The CC genotype was higher than the TT genotype (P = .003) and CT versus the TT (P = .009). In patients with PE, the CC genotype was higher than the TT genotype (P = .038). Pulmonary embolism with massive and submassive events had predominant genotypes 677 TT (P = .003) and the AA 1298 (P = .017). Elevated Hcy levels in the presence of the T allele in the C677T gene and of the A allele in the A1298C gene are associated with AMI and massive and submassive PE.